2018
DOI: 10.7150/ijbs.23542
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Suppresses Proliferation and Migration in Non-small Cell Lung Cancer via Pyroptosis

Abstract: Pyroptosis is a form of caspase-1-dependent programmed cell death with anti-tumor properties, but the underlying molecular mechanisms are not fully understood. The results of our study showed that the antihyperlipidemic drug simvastatin induced pyroptosis in non-small cell lung cancer (NSCLC) cell lines and a xenograft mouse model. Inhibition of pyroptosis attenuated the effects of simvastatin on tumor cell viability and migration. These data suggest that simvastatin may induce pyroptosis, thereby potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 24 publications
0
88
0
Order By: Relevance
“…Recent evidences suggested that multiple signaling pathways and various types of cell death may be activated in single dying cells [55,56], and ROS, as a trigger, can lead to various types of regulated cell death (RCD) [55,57,58]. Furthermore, these RCD share some common mechanisms [59], and many compounds, such as simvastatin, paclitaxel, cisplatin, etc., were reported to induce autophagy, apoptosis and pyroptosis in NSCLC [31,52,[60][61][62][63][64]. Therefore, we suspected that PPVI might also induce pyroptotic cell death in NSCLC via increased ROS levels.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recent evidences suggested that multiple signaling pathways and various types of cell death may be activated in single dying cells [55,56], and ROS, as a trigger, can lead to various types of regulated cell death (RCD) [55,57,58]. Furthermore, these RCD share some common mechanisms [59], and many compounds, such as simvastatin, paclitaxel, cisplatin, etc., were reported to induce autophagy, apoptosis and pyroptosis in NSCLC [31,52,[60][61][62][63][64]. Therefore, we suspected that PPVI might also induce pyroptotic cell death in NSCLC via increased ROS levels.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, some chemicals were reported to suppress the proliferation of NSCLC cells via the activation of pyroptosis. For example, simvastatin suppresses proliferation and migration in vitro and in vivo by inducing pyroptosis via activating NLRP3-caspase-1-IL-1β and IL-18 pathways [31]. In addition, cisplatin was reported to induce higher levels of secondary necrosis/pyroptosis in A549 cells via the caspase-3/GSDME activation [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed the roles of pyroptosis in several types of cancers, including colon cancer, gastric cancer, lung cancer, breast cancer, liver cancer, and glioma. However, no studies have focused on the pyroptosis in PDAC (18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that pyroptosis aggravates hepatic fibrosis diabetes and diabetic cardiomyopathy 25,26 . A recent study of tumor cells showed that induction of caspase-1-mediated pyroptosis by simvastatin in non-small-cell lung cancer (NSCLC) promoted cell death and exerted antitumor effects 27 . Caspase-1 is downregulated in many cancer types, and its loss enhances tumor formation and promotes cancer development 27,28 .…”
Section: Introductionmentioning
confidence: 99%